Subspecies and Distribution. L.a.americanusErxleben,1777—C&ECanada(SENorthwestTerritories,SENunavut,mostAlberta,Saskatchewan,andManitoba,S&SEOntario,Quebec,L.a.,andNewfoundland),alsoinNCUSA(NEMontanaandNorthDakota). L.a.bairdiiHayden,1869—SWCanada(SEBritishColumbiaandSWAlberta)andWCUSA(W&CMontana,Idaho,W&SCWyoming,NE&CUtah,NW&CColorado,andNCNewMexico). L.a.cascadensisNelson,1907—SWCanada(SCBritishColumbia)andNWUSA(SC,C&NCWashington). L.a.columbiensisRhoads,1895—RockyMtsinSWCanada(SEBritishColumbia,WCAlberta),andNWUSA(NEtipofWashington). L.a.dalliMerriam,1900—Alaska(USA)andNWCanada(NWAlberta,NBritishColumbia,YukonexcepttheNtip,S&WNorthwestTerritories). L.a.klamathensisMerriam,1899—WUSA(SWOregonandNCalifornia). L.a.oregonusOrr,1934—WUSA(NE&COregon). L.a.pallidusCowan,1938—SWCanada(WC&CBritishColumbia). L.a.phaeonotusJ.A.Allen,1899—WGreatL.a.RegioninSCCanada(SEtipofSaskatchewan,SManitoba,SWOntario)andNCUSA(NEtipofNorthDakota,Minnesota,NWisconsin,andNMichigan). L.a.pineusDalquest,1942—SWCanada(SCtipofBritishColumbia)andNWUSA(EWashington,NIdaho,NWtipofMontana). L.a.seclususBaker&Hankins,1950—NCUSA(SCtipofMontana,NCtipofWyoming). L.a.struthopusBangs,1898—ECanada(EQuebec,NewBrunswick,NovaScotia,PrinceEdwardI)andNEUSA(Maine). L.a.tahoensisOrr,1933—WUSA(ECCaliforniaandWCNevada). L.a.virgtnianusHarlan,1825—SECanada(SOntario,SQuebec)andNE&EUSA(fromMainetoPennsylvaniaandextremeNEOhio,TennesseeandNorthCarolina). L. a. washingtonBaird, 1855 — SW Canada (SW tip of British Columbia) and NW USA (W Washington and W Oregon). The Snowshoe Hare has been introduced by founder individuals of unknown subspecies affiliation to Kodiak I (Alaska) and Anticosti I (Quebec, Canada). in Leporidae - Don E. Wilson; Thomas E. Lacher, Jr; Russell A. Mittermeier (Lynx Edicions, 2016)
Subspecies and Distribution. L.a.americanusErxleben,1777—C&ECanada(SENorthwestTerritories,SENunavut,mostAlberta,Saskatchewan,andManitoba,S&SEOntario,Quebec,L.a.,andNewfoundland),alsoinNCUSA(NEMontanaandNorthDakota). L.a.bairdiiHayden,1869—SWCanada(SEBritishColumbiaandSWAlberta)andWCUSA(W&CMontana,Idaho,W&SCWyoming,NE&CUtah,NW&CColorado,andNCNewMexico). L.a.cascadensisNelson,1907—SWCanada(SCBritishColumbia)andNWUSA(SC,C&NCWashington). L.a.columbiensisRhoads,1895—RockyMtsinSWCanada(SEBritishColumbia,WCAlberta),andNWUSA(NEtipofWashington). L.a.dalliMerriam,1900—Alaska(USA)andNWCanada(NWAlberta,NBritishColumbia,YukonexcepttheNtip,S&WNorthwestTerritories). L.a.klamathensisMerriam,1899—WUSA(SWOregonandNCalifornia). L.a.oregonusOrr,1934—WUSA(NE&COregon). L.a.pallidusCowan,1938—SWCanada(WC&CBritishColumbia). L.a.phaeonotusJ.A.Allen,1899—WGreatL.a.RegioninSCCanada(SEtipofSaskatchewan,SManitoba,SWOntario)andNCUSA(NEtipofNorthDakota,Minnesota,NWisconsin,andNMichigan). L.a.pineusDalquest,1942—SWCanada(SCtipofBritishColumbia)andNWUSA(EWashington,NIdaho,NWtipofMontana). L.a.seclususBaker&Hankins,1950—NCUSA(SCtipofMontana,NCtipofWyoming). L.a.struthopusBangs,1898—ECanada(EQuebec,NewBrunswick,NovaScotia,PrinceEdwardI)andNEUSA(Maine). L.a.tahoensisOrr,1933—WUSA(ECCaliforniaandWCNevada). L.a.virgtnianusHarlan,1825—SECanada(SOntario,SQuebec)andNE&EUSA(fromMainetoPennsylvaniaandextremeNEOhio,TennesseeandNorthCarolina). L. a. washingtonBaird, 1855 — SW Canada (SW tip of British Columbia) and NW USA (W Washington and W Oregon). The Snowshoe Hare has been introduced by founder individuals of unknown subspecies affiliation to Kodiak I (Alaska) and Anticosti I (Quebec, Canada). Published as part of Don E. Wilson, Thomas E. Lacher, Jr & Russell A. Mittermeier, 2016, Leporidae, pp. 107-148 in Handbook of the Mammals of the World – Volume 6 Lagomorphs and Rodents I, Barcelona :Lynx Edicions on page 135, DOI: 10.5281/zenodo.6625539